Binapthyl Schiff base diamine complex covalently bonded to modified SBA-15: synthesis, characterization and catalytic application - Sharma, Priti; Singh, A. P. (Catalysis Today, 2012)
Protected mesoporous SBA-15 phase was synthesized by grafting the complex Chloro (S,S)(-)[N-3-tert-butyl-5-chloromethyl salicylidene]-N'-[3',5'-di tert-butyl salicylidene] 1,1'-binapthyl-2,2'-diamine manganese(III) through the reactive 3-aminopropyl trimethoxysilane(3-APTMS) group. The surface properties of the functionalized catalyst were analyzed by a series of characterization techniques like elemental analysis, XRD, N-2 sorption measurement isotherm, FT-IR, XPS, and solid state C-13 NMR. The screening of the catalyst Mn(III)-L-SBA-15 and neat Mn(III)-L complexes was done for the oxidation reaction of thioanisole (methyl phenyl sulfide) using TBHP as an oxidant. Mn(III)-L-SBA-15 catalyst shows higher activities and exhibit enantiomeric excess comparable to homogeneous catalyst. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: -OH protected NH2-SBA-15; Binaphthyl Schiff base ligand; Ordered mesoporous materials; Sulfoxidation; Thioanisole

Disordered mesoporous V/TiO2 system for ambient oxidation of sulfides to sulfoxides - Negi, Sanjay Singh; Sivaranjani, Kumarsrinivasan; Singh, Anand Pal; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2013)
High sulfide conversion and predominant sulfoxide yield has been observed with 0.1% vanadium doped disordered mesoporous Ti1-xVxO2 material at ambient and sub ambient temperatures using environmentally green H2O2 oxidant. Ti1-xVxO2 materials were prepared by one-pot solution combustion method in less than 15 min and thoroughly characterized by X-ray diffraction, HRTEM, Raman spectra and other physicochemical techniques. Different sulfides, such as, phenylsulfide, methyl-p-tolylsulfide, ethylsulfide, thioanisole, were converted into the corresponding sulfoxide. Isolated V5+ incorporated in the TiO2 lattice is likely to be the active species for the sulfide oxidation reaction. Catalyst recycling studies indicates the robustness of the catalyst. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Ambient oxidation; Combustion synthesis; heterogeneous catalysis; Hydrogen peroxide; Mesoporous TiO2; Sulfoxidation; Sulfoxide